KAP Method (Know-And-Practice) for Increasing Self-Control as a Preventive Effort to Minimize Deviant Sexual Fantasies in Adolescents Aged 16-20 Years - Evelin, Patricia Viona; Aufizzahra As Syafiyah; Disa Aulya Nanda; Ely Hariani; Yusi Nadila (Causalita, 2024)
Adolescents are individuals who are in the transition period from children to adults who experience biological, psychological and social changes. During adolescence, individuals will experience sexual maturity and then they will tend to look for various information about sex due to their high curiosity about sexual content. One of teenagers' curiosity about sexual content that can have a negative effect on themselves is deviant sexual fantasies. In overcoming this problem, namely by realizing the term KAP (Know-And-Practice) in research, namely so that subjects are able to increase their understanding regarding the importance of good self-control as a form of preventing the occurrence of deviant sexual fantasies in a group, community and society. This research aims to increase understanding and skills as a preventative effort for the emergence and/or spread of psychological disorders in a group, community and society and to see how much influence psychoeducation has on each aspect of the research. The research design uses a quantitative experimental approach with a pre-experimental research design, one group pre-test post-test, in this study there is no control group. The participants in this research were teenagers aged 16-20 years, consisting of 15 male teenagers. The results of this research show that the KAP (Know-And-Practice) method has an effective effect in increasing understanding regarding the importance of good self-control as a form of preventing the occurrence of deviant sexual fantasies in a group, community and society.